Clinical efficacy of dexmedetomidine combined with lidocaine for femoral and sciatic nerve blocks in dogs undergoing stifle surgery. (November 2021) - Acquafredda, Claudia; Stabile, Marzia; Lacitignola, Luca; Centonze, Paola; Di Bella, Caterina; Crovace, Antonio; Fiorentino, Marco; Staffieri, Francesco
Abstract: Objective: To evaluate the effects of dexmedetomidine administered perineurally or intramuscularly (IM) on sensory, motor function and postoperative analgesia produced by lidocaine for sciatic and femoral nerve blocks in dogs undergoing unilateral tibial tuberosity advancement surgery. Study design: Prospective, blinded, clinical study. Animals: A group of 30 dogs. Methods: Dogs were anaesthetized with acepromazine, propofol and isoflurane in oxygen/air. Electrolocation-guided femoral and sciatic nerve blocks were performed: group L, 0.15 mL kg –1 2% lidocaine ( n  = 10); group LDloc, lidocaine and 0.15 μg kg –1 dexmedetomidine perineurally ( n  = 10); group LDsys, lidocaine and 0.3 μg kg –1 dexmedetomidine IM ( n  = 10). After anaesthesia, sensory blockade was evaluated by response to forceps pinch on skin innervated by the saphenous/femoral, common fibular and tibial nerves. Motor blockade was evaluated by observing the ability to walk and proprioception. Analgesia was monitored with Short Form of Glasgow Composite Pain Scale for up to 4 hours after extubation. Methadone IM was administered as rescue analgesia. Data were analysed by linear mixed effect models and Kaplan-Meier test ( p < 0.05). Results: Median duration of the sensory blockade for all nerves was longer ( p < 0.001) for group LDloc than for groups L and LDsys and was longer ( p  = 0.0011) for group LDsys than for group L. Proprioception returned later ( p < 0.001) for group LDloc [285 (221–328) minutes] compared with group L [160 (134–179) minutes] or LDsys [195 (162–257) minutes]. Return of the ability to walk was similar among all groups. Dogs in group LDloc required postoperative rescue analgesia later ( p  = 0.001) than dogs in groups LDsys and L. Conclusions and clinical relevance: Dexmedetomidine administered perineurally with lidocaine prolonged sensory blockade and analgesia during the immediate postoperative period. Systemic dexmedetomidine also prolonged the sensory blockade of perineural lidocaine.